2017
DOI: 10.4049/jimmunol.1700232
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Long Noncoding RNAs in Human Naive and Memory T Cells

Abstract: We employed whole genome RNA-sequencing to profile mRNAs and both annotated and novel long noncoding RNAs (lncRNAs) in human naïve, central memory and effector memory CD4+ T cells. Loci transcribing both lineage-specific annotated and novel are adjacent to lineage-specific protein-coding genes in the genome. Lineage-specific novel lncRNA loci are transcribed from lineage specific typical- and super-transcriptional enhancers and are not multi-exonic, thus are more similar to enhancers RNAs. Novel enhancer assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…In addition to promoter-enhancer looping and histone modifications, eRNAs interact with transcriptional machinery such as transcription factors, BRD4, and RNAP II. eRNA knockdown decreases binding of transcription factors at respective promoter and enhancer loci, perhaps due to loss of the "transcription factor trapping" mechanism previously discussed (Sigova et al, 2015;Spurlock et al, 2017;Huang Z. et al, 2018). Additionally, the bromodomains of BRD4 have been shown to directly interact with eRNA.…”
Section: Regulation Of Transcriptional Machinerymentioning
confidence: 98%
See 2 more Smart Citations
“…In addition to promoter-enhancer looping and histone modifications, eRNAs interact with transcriptional machinery such as transcription factors, BRD4, and RNAP II. eRNA knockdown decreases binding of transcription factors at respective promoter and enhancer loci, perhaps due to loss of the "transcription factor trapping" mechanism previously discussed (Sigova et al, 2015;Spurlock et al, 2017;Huang Z. et al, 2018). Additionally, the bromodomains of BRD4 have been shown to directly interact with eRNA.…”
Section: Regulation Of Transcriptional Machinerymentioning
confidence: 98%
“…RNAs tethered near enhancer loci were shown to increase the presence of YY1 specifically at those loci, perhaps due to "transcription factor trapping" wherein nascent RNA from enhancers and promoters increase the affinity of otherwise weak DNA-TF interactions creating a kinetic sink that would "trap" escaped transcription factors (Sigova et al, 2015). Such a model may explain observations that eRNA increases the binding of transcription factors such as c-Jun and NF-κB to target loci (Shii et al, 2017;Spurlock et al, 2017;Huang Z. et al, 2018). An emerging idea for how eRNAs may interact with large numbers of proteins is through phase separation.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that NeST RNA interacts with the epigenetic modifier WDR5 to promote the transcription of Ifng in CD4 + and CD8 + T cells thus conferring the observed differences in Theiler's virus infection between mouse strains. These data have been further corroborated in human T cells—specifically Th1 cells, which display diminished IFNg induction upon depletion of NEST …”
Section: Lncrnas In Host‐virus Interactionsmentioning
confidence: 60%
“…Many lineage-specific lncRNAs were reported, most of them mapped in a non-random manner, positioned close to the lineage-specific protein-coding genes with which they are co-expressed. Furthermore, it has been demonstrated that lncRNAs mapped near to the IFNG locus are necessary for IFNG prompt expression, since the expression inhibition of lncRNAs IFNG-AS1 and IFNG-R-49 by siRNAs abolishes IFNG expression by effector memory T lymphocytes [ 49 ].…”
Section: Long Non-coding Rnas: Expression Patterns In Tissues or Cmentioning
confidence: 99%